World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonization Project: III. Fluid biospecimen collection, processing, and storage in endometriosis research. - Rahmioglu, N; Fassbender, A; Vitonis, A; Tworoger, S; Hummelshoj, L; D'Hooghe, T; Adamson, G; Giudice, L; Becker, C; Zondervan, K; Missmer, SA (Elsevier, 2014)
OBJECTIVE: To harmonize standard operating procedures (SOPs) and standardize the recording of associated data for collection, processing, and storage of fluid biospecimens relevant to endometriosis. DESIGN: An international collaboration involving 34 clinical/academic centers and 3 industry collaborators from 16 countries on 5 continents. SETTING: In 2013, 2 workshops were conducted, followed by global consultation, bringing together 54 leaders in endometriosis research and sample processing worldwide. PATIENT(S): None. INTERVENTION(S): Consensus SOPs were based on: [1] systematic comparison of SOPs from 18 global centers collecting fluid samples from women with and without endometriosis on a medium/large scale (publication on >100 cases), [2] literature evidence where available, or consultation with laboratory experts otherwise, and [3] several global consultation rounds. MAIN OUTCOME MEASURE(S): Standard recommended and minimum required SOPs for biofluid collection, processing, and storage in endometriosis research. RESULT(S): We developed recommended standard and minimum required SOPs for the collection, processing, and storage of plasma, serum, saliva, urine, endometrial/peritoneal fluid, and menstrual effluent, and a biospecimen data-collection form necessary for interpretation of sample-derived results. CONCLUSION(S): The Endometriosis Phenome and Biobanking Harmonisation Project SOPs allow endometriosis research centers to decrease variability in biofluid sample results, facilitating between-center comparisons and collaborations. The procedures are also relevant to research into other female conditions involving biofluid samples subject to cyclic reproductive influences. The consensus SOPs are based on the best available evidence; areas with limited evidence are identified as requiring further pilot studies. The SOPs will be reviewed based on investigator feedback, and through systematic tri-annual follow-up. Updated versions will be made available at: endometriosisfoundation.org/ephect.